Value of Spectrum for Mobile Communications: Case of Korea - Yongkyu Kim; Kiwon Kim; Yunjeong Jang; Seungkeun Park (International Telecommunications Society (ITS), 2022)
Evaluation of spectrum price is important for most of the regulatory bodies and for most mobile operators. In some cases, regulatory authority faces a situation to evaluate the value of the radio spectrum which has been allocated already. In Korea, there was a reallocation of most of the LTE spectrum bands in 2020. In this paper, we propose a method to evaluate the value of each band based on the band's capacity out of total capacity. In addition, if we can find a reasonable value of the overall spectrum band, we can find a value for each band together with the information in the first stage. This method can be easily applied if only the regulatory authority has detailed geotype information on base transceiver stations(BTS).
Keywords: 330; value of spectrum; base transceiver station; LTE; spectrum band; production function